Laughter is the best medicine: The Second City® improvisation as an intervention for Parkinson's disease. (January 2017) - Bega, Danny; Palmentera, Pamela; Wagner, Abby; Hovde, Matt; Barish, Becca; Kwasny, Mary J.; Simuni, Tanya
Abstract: Background: Expressive therapies are increasingly incorporated into the management of Parkinson's disease (PD), although there are little objective data assessing their benefits. Objective: Develop and study a novel community Improvisation Theater (IT) program for PD in order to improve quality of life. Methods: A prospective, rater-blinded, modified cross-over design study of IT for PD. 22 subjects were randomized 1:1 to active-start (AS) or control-start (CS) groups, controlling for age and Hoehn and Yahr stage. Participants were recruited from the Northwestern PD and Movement Disorders Center. 60 min IT sessions were led by The Second City ® faculty weekly for 12 weeks. The primary aim was to assess feasibility, determined as 70% of participants attending at least 75% of the classes. Exploratory data were obtained comparing pre- and post-intervention outcomes using Wilcoxon signed rank test for UPDRS parts I-IV, PDQ-39, and 5 neuro-QoL measures (communication, anxiety, stigma, depression, and wellbeing). Results: All 22 participants completed the study. 21/22 (95%) participants attended at least 80% of the classes. All participants indicated that they would recommend the class to others with PD. 21/22 participants enjoyed the class and felt it was beneficial for their symptoms. A significant improvement pre-to-post intervention was seen with the UPDRS part II ADL measure (mean −1.5, p = 0.019). Conclusion: A novel improvisation program can be well-attended, enjoyable, and improve ADL measures among patients with PD of varying ages and disease severity. Highlights: Improvisation may cultivate focus, improve communication, and promote well-being. People with PD enjoy improv classes and feel it is beneficial for their PD symptoms. Improv training can lead to improvement in activities of daily living in PD.